Propuesta de Diseño de Planta Para la Empresa Carnicería Santa Fe de Santa Marta, Magdalena - Barbosa Redondo, Santiago David; Villa Cantillo, Diego Elías (Universidad Antonio Nariño, 2022)
During the investigative study within the Santa Fe butcher's shop, we opted to choose systematized and computer methods, starting with the use in the first specific objective, of an interview based on the Ishikawa diagram, in this way to know the most deficient indexes in their study factors, and the characterization of processes, machines and tools within the company, for the second specific objective we chose to introduce the System Layout Planning (SLP), we were able to complete the steps stated in this method, which were composed of diagrams of both path, relationship between activities, graph of nodes and threads for the relationship between activities, and finally an analysis of needs and spaces with their respective graph of nodes and threads. We also made use of the CRAFT method for the redistribution of human-machine, within the company, based on the cost of movement, travel flow, and distance distributed within the work plan of the company, demonstrating graphically through plans with their respective tables of total cost, thus choosing the most minimized response, which suits the company. While for the third and last specific objective, we were able to program a simulation thanks to the ARENA application, which gave us a more updated way to demonstrate that the plant design proposal provided by us, had significant changes from the distribution of the machines, and distance traveled during the main process of the company, compared to the mechanism that was currently installed.